River management, landuse change, and future flood risk in China's Poyang Lake region - Shankman, D.; Davis, L.; Leeuw, Jan de (Informa UK Limited, 2009)
Poyang Lake is the largest freshwater lake in China covering 3800 km2 during the summer wet season. It drains into the Changjiang (Yangtze River) at its northern end through a narrow outlet. During the last half of the twentieth century (1949–1999) average annual maximum stage and number of severe flood events in China's Poyang Lake region increased significantly. There are two primary causes for this trend. One was increasing Changjiang stage, which is the most important determinant of Poyang Lake stage. The second cause for increasing lake stage was levee construction at the margins of Poyang Lake that greatly limited lake size, and therefore, reduced floodwater storage. More recent changes affecting future flood risk include completion of the Three?Gorges Dam, which was intended for flood?control. The Three?Gorges Dam can be used to hold back floodwater for common annual floods, but the reservoir's storage capacity is too small to reduce downstream discharge during the most severe floods. Also, flood control policies were modified during the past decade, and now focus on permanent removal of some levees and the opening of others during severe floods to increase floodwater storage. These policies have not been fully implemented, and the threat of severe floods affecting densely populated areas in the Poyang Lake region has not been eliminated.